Reconsidering Institutional Research Policies on Indigenous Collections - Laura Bryant; Marla Taylor; Laura Elliff Cruz (Advances in Archaeological Practice)
The fields of archaeology and museology are working to encourage and enforce research methodologies and policies that center reciprocity and respect among archaeologists, institutions, and Native Nations. This shift in approach is grounded in part by the inclusion of the Duty of Care clause in the revised NAGPRA regulations and partly by a revised awareness of ethical standards. Policy-level changes around research access are the most impactful but can also be the most challenging to initiate. In this article, we address shifts in both institutional research policies and researchers’ approaches and practices that actively incorporate Native perspectives. The framework presented was developed as a complement to the Indigenous Collections Care Guide and is grounded in case studies from three institutions that have changed their research policies. The resulting prompts, tips, examples, and challenges are provided for both researchers and institutions to evaluate research and access practices and how they intersect with Native perspectives. Seeking input and consent from Native Nations adds challenging layers to research, but the depth, quality, and impact of the research and the strengthening of relationships and trust with the communities significantly outweigh the extra time and effort.